Digital Community Hub in Serpong, Tangerang Selatan (An Eco-Technology Architecture) - Kristi, Nandini Anindita; Wibisono, Adryanto Ibnu (Journal of Aesthetics, Creativity and Art Management, 2024)
Serpong District in South Tangerang, Banten Province, Indonesia, is an area that has the greatest potential for creative economic development but does not yet have facilities capable of accommodating this activity. Therefore, a digital community hub is needed that can fulfill the facilities and needs for the development of the creative economy in the fields of information and technology. It is necessary to plan and design the digital community hub that pays attention to and responds to climate and environmental conditions by applying eco-technological architectural concepts, to obtain a building design that is responsive and in harmony with the surrounding environment. Methodologically, the application of the concept of eco-technology architecture includes the application of design strategies for energy efficiency and adding value to the quality of buildings for the environment, utilization of renewable energy, selection of materials and openings in buildings. Its design is divided into four zonings, namely, rental office zoning, digital capability development zoning, culinary zoning and service zoning. In its operation and maintenance, this building utilizes energy efficiency in the use of water and lighting. The green roof which is used as a communal space adds aesthetic value while supporting the eco-technological architectural concept implemented.